4m-9=5m+7

Simple and best practice solution for 4m-9=5m+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m-9=5m+7 equation:


Simplifying
4m + -9 = 5m + 7

Reorder the terms:
-9 + 4m = 5m + 7

Reorder the terms:
-9 + 4m = 7 + 5m

Solving
-9 + 4m = 7 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.
-9 + 4m + -5m = 7 + 5m + -5m

Combine like terms: 4m + -5m = -1m
-9 + -1m = 7 + 5m + -5m

Combine like terms: 5m + -5m = 0
-9 + -1m = 7 + 0
-9 + -1m = 7

Add '9' to each side of the equation.
-9 + 9 + -1m = 7 + 9

Combine like terms: -9 + 9 = 0
0 + -1m = 7 + 9
-1m = 7 + 9

Combine like terms: 7 + 9 = 16
-1m = 16

Divide each side by '-1'.
m = -16

Simplifying
m = -16

See similar equations:

| 12.6n+-5.2n= | | -t+10=t+4 | | 8y-6=5y+12 | | 3x+10=85 | | 2x=x+4 | | ah= | | ha= | | men= | | 14=3y | | 8t^2-2t-3=0 | | 6b+5-6b= | | 2x-6= | | 4x+9=2x+6 | | 6x+4y=15 | | 2.5(2t-8v)-3(3v+1.5t)= | | -5(2-6x)-7(1-7x)=62 | | 5a+5b= | | 12x+-9=22 | | 7(1.8n-4)+13-5.2n= | | 1.5q=-8.4 | | 2x-5(x+1)=4x+3 | | 4c-5=2c+5 | | 9(a+1.4b)+8(b-16a)= | | x^3+10x= | | 2+4(-6n+5)=2n-4 | | -3t=-4.2 | | 4.2x+8.1x+1.8x-(2.1x)= | | 3(5+4b)-2= | | 8w+20=12w-9 | | 4.2x+8.1x+1.8x-2.1x= | | r+11=-8r+29 | | -7n=35 |

Equations solver categories